Construction of ecological security pattern in coastal urban areas: A case study in Qingdao, China - Qian, Wenqi; Zhao, Ye; Li, Xiaoyu (Ecological indicators, 2023)
•An innovative framework for ecological conservation in coastal urban areas.•Apply the circuit theory to extract ecological corridors.•Constructing the ESP from the perspective of “surfaces-lines-points”. The accelerated urbanization process has led to the deterioration of the originally fragile coastal ecosystem, whose slight changes in ecological environment may destroy the original coastal urban ecosystem. The construction of the ecological security pattern can effectively balance the development of coastal urban areas and the protection of ecological environment. This study proposes a new framework for constructing ESP in coastal urban areas: surfaces (ecological sources) - lines (ecological networks) - points (pinch points, barrier points). The ecological sources were identified by morphospatial pattern analysis and landscape connectivity. Then, the ecological network and ESP were constructed by the circuit theory. Take Qingdao, a typical coastal urban area with a very fragile ecological environment, as the subject of the study. The results indicate that: (1) the landscape connectivity of ecological source sites identified in 2017 and 2021 has decreased significantly; (2) the total length of extracted ecological corridors has decreased dramatically; (3) the ESP of Qingdao was constructed from the perspective of surfaces - lines - points. The results of this paper can provide scientific planning guidance for the conservation and protection of ecological security in Qingdao. The research framework proposed in this paper provides some reference for the conservation of the ecological environment in coastal urban areas.